Identification and Physicochemical Properties of the Novel Hemolysin(s) From Oral Secretions of Helicoverpa armigera (Lepidoptera: Noctuidae). Issue 6 (9th November 2021) - Wang, Xiong-Ya; Cai, Dong-Zhang; Li, Xin; Bai, Su-Fen; Yan, Feng-Ming
Abstract: Hemolysins cause the lysis of invading organisms, representing major humoral immunity used by invertebrates. Hemolysins have been discovered in hemolymph of Helicoverpa armigera larvae as immune factors. As oral immunity is great important to clear general pathogens, we presumed that hemolysins may be present in oral secretions (OS). To confirm this hypothesis, we conducted four testing methods to identify hemolysin(s) in larval OS of H. armigera, and analyzed physicochemical properties of the hemolysin in comparison with hemolytic melittin of Apis mellifera (L.) (Hymenoptera: Apidae) venom. We found hemolysin(s) from OS of H. armigera for the first time, and further identified in other lepidopteran herbivores. It could be precipitated by ammonium sulfate, which demonstrates that the hemolytic factor is proteinaceous. Labial gland showed significantly higher hemolytic activity than gut tissues, suggesting that hemolysin of OS is mainly derived from saliva secreted by labial glands. Physicochemical properties of hemolysin in caterpillar's OS were different from bee venom. It was noteworthy that hemolytic activity of OS was only partially inhibited even at 100°C. Hemolytic activity of OS was not inhibited by nine tested carbohydrates contrary to bee venom melittin. Moreover, effects of metal ions on hemolytic activity were different between OS and bee venom. We conclude that there is at least a novel hemolysin in OS of herbivorous insects with proposed antibacterial function, and its hemolytic mechanism may be different from melittin. Our study enriches understanding of the potential role of hemolysins in insect immunity and provides useful data to the field of herbivorous insect-pathogen research. Graphical Abstract: